The Trans-Neptunian Solar System 2020
DOI: 10.1016/b978-0-12-816490-7.00006-0
|View full text |Cite
|
Sign up to set email alerts
|

Volatile evolution and atmospheres of Trans-Neptunian objects

Abstract: At 30-50 K, the temperatures typical for surfaces in the Kuiper Belt (e.g. Stern & Trafton 2008), only seven species have sublimation pressures higher than 1 nbar (Fray & Schmitt 2009): Ne, N 2 , CO, Ar, O 2 , CH 4 , and Kr. Of these, N 2 , CO, and CH 4 have been detected or inferred on the surfaces of Trans-Neptunian Objects (TNOs). The presence of tenuous atmospheres above these volatile ices depends on the sublimation pressures, which are very sensitive to the composition, temperatures, and mixing states of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 135 publications
0
6
0
Order By: Relevance
“…Being very stable at low temperature, it is very abundant in the Earth atmosphere, and is notably present in other planetary atmospheres -Titan 98.4 % 1 , Triton 2 Pluto 3 , Venus 3.5 % and Mars 1.9 % 1 . For other trans-Neptunian objects than Pluto, this molecule is also one of the main component of the ices -spectroscopically observed at their surfaces -and may produce a very thin atmosphere when the temperature increases under solar irradiation 4 . Under the influence of an electric field, the high altitude planetary atmosphere can be crossed by few milliseconds giant discharges called sprites, whose spectroscopic signature is mainly due to spontaneous emission from N 2 excited electronic states 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Being very stable at low temperature, it is very abundant in the Earth atmosphere, and is notably present in other planetary atmospheres -Titan 98.4 % 1 , Triton 2 Pluto 3 , Venus 3.5 % and Mars 1.9 % 1 . For other trans-Neptunian objects than Pluto, this molecule is also one of the main component of the ices -spectroscopically observed at their surfaces -and may produce a very thin atmosphere when the temperature increases under solar irradiation 4 . Under the influence of an electric field, the high altitude planetary atmosphere can be crossed by few milliseconds giant discharges called sprites, whose spectroscopic signature is mainly due to spontaneous emission from N 2 excited electronic states 5 .…”
Section: Introductionmentioning
confidence: 99%
“…members of this group at some point in their orbits, although the presence of an atmosphere remains to be confirmed (Young et al, 2020). Bertrand et al (2020) have studied the surface-atmosphere interactions at Pluto and their impact on the near surface winds and the atmospheric general circulation by using a 3D GCM adapted to Pluto.…”
Section: Yung)mentioning
confidence: 99%
“…Pluto is one of four solar system objects on which the atmospheric column abundance of its primary gas components is known to be controlled by the vapor pressure of surface ices, the other three being Triton, Io, and Mars. Eris and other large trans-Neptunian objects are also likely members of this group at some point in their orbits, although the presence of an atmosphere remains to be confirmed (Young et al, 2020). Bertrand et al (2020) have studied the surface-atmosphere interactions at Pluto and their impact on the near surface winds and the atmospheric general circulation by using a 3D GCM adapted to Pluto.…”
Section: Introductionmentioning
confidence: 99%
“…It is plausible that the surfaces of Makemake and Eris are similarly refreshed by atmospheric processes, resulting in their bright surfaces and their very small rotational lightcurve amplitudes (e.g., Heinze & de Lahunta 2009, Sicardy et al 2011, Ortiz et al 2012, Hofgartner et al 2019. Models have indicated that these two worlds could host regional or global vapor pressure equilibrium atmospheres of N 2 and/or CH 4 at some points in their orbits (e.g., Stern & Trafton 2008, Young 2015, though searches for atmospheres through stellar occultation measurements have yielded no detectable global atmospheres to date (see Young et al 2020 for a review). Stellar occultationbased upper limits of surface pressures have been made for Eris (Sicardy et al 2011), Haumea (Ortiz et al (2017, Makemake (Ortiz et al 2012), and Quaoar (Arimatsu et al 2019b); the 1σ upper limits range from 1-12×10 −9 bar.…”
Section: Surface Composition Atmospheres and Volatile Transportmentioning
confidence: 99%